Burkitt Lymphoma of the Duodenum: An Uncommon Phenomenon - Fahad Malik; Manuel Gonzalez; Wahib Zafar (Case Reports in Gastrointestinal Medicine)
Burkitt lymphoma is an aggressively growing tumor commonly found in African children, involving the jaw and facial bones. Most non-Hodgkin lymphoma tumors involve extra nodal sites like the nervous system and gastrointestinal tract. A rare variant of this type of lymphoma is found in immunocompromised patients specifically in the gastrointestinal tract with accompanying gastrointestinal symptoms. Burkitt lymphoma is a malignancy that has commonly presented in GI tract but rarely in the duodenum. This clinical variant can commonly involve stomach, ileum, and cecum. However, there is very limited data available regarding the duodenal growth of this tumor. Duodenal involvement of Burkitt lymphoma is extremely rare and accounts for < 1% of all lymphomas. We present a case report of an older patient with a duodenal Burkitt lymphoma diagnosed by biopsy. A high suspicion should be present while treating immunocompromised patients with chronic abdominal symptoms especially with complications such as bleeding or occult positive testing. Early endoscopy intervention with biopsy can help identity and treat these conditions with improved outcomes for the patients.